Utilization of Digital Literacy in Increasing the Number of Customers Using Digital Saving - Paradiesta, Alifia Diva; Isnawati, Setya Indah (Golden Ratio of Data in Summary, 2024)
This study aims to explore the use of digital literacy in increasing the number of customers using digital saving services at PT Bank Rakyat Indonesia Parakan Branch Office. The focus of the research includes how digital literacy can increase the number of customers, the obstacles faced in the application of digital saving services, and the efforts made to optimize the application of these services. This type of research is descriptive qualitative research. The sampling technique used purposive sampling with a total of 10 informants consisting of BRI KC Parakan employees and several customers. Research instruments include in-depth interviews, observation, and documentation. The collected data were analyzed using thematic analysis method to identify the main themes that emerged from the data. The results showed that the implementation of digital literacy through social media, direct socialization, and education by customer service played a significant role in increasing customer understanding and trust in digital saving services. This study concludes that digital literacy plays an important role in increasing the number of customers using digital saving services at BRI KC Parakan. Technical barriers and lack of customer understanding are the main challenges in implementing this service. It is hoped that by implementing the suggestions that have been identified, BRI KC Parakan can further optimize the implementation of digital saving services in the future.